Evaluation of Physical Symptoms in Patients on Peritoneal Dialysis - Ana Elizabeth Figueiredo; Cate Goodlad; Michelle Clemenger; San San Haddoub; Jacqueline McGrory; Kim Pryde; Emma Tonkins; Nora Hisole; Edwina Anne Brown (International Journal of Nephrology)
Introduction. Little is known about physical symptoms in peritoneal dialysis (PD) Patients. This study aims to determine the prevalence of symptoms (general and abdominal) in PD patients. Methods. A cross-sectional study, with subsequent followup, using an author-designed 21 symptoms questionnaire (15 nonabdominal and 6 abdominal). Each symptom was assessed on a scale 0–3 for severity (none–severe) and frequency (never–every day). Results. We studied 41 patients, mean age years, 56% male, 19.5% diabetics, and 51.5% on APD. Mean number of symptoms was and total symptoms score was with abdominal scores of . Most frequent symptoms were lack of energy, itching, cramps, poor sleep, and loss of appetite. A second evaluation in 20 patients disclosed no statistical difference between the first and second assessments, or between subgroups. Cramps were the only symptoms which decreased over time (). Lack of energy did not correlate with haemoglobin, neither did itching with phosphate level. Conclusions. Physical symptoms are frequent and troublesome; they relate to advanced kidney disease and not specifically to PD. Symptoms remain stable over time and do not appear to relate to dialysis parameter markers.